Surgical Burden and Centralisation of Hepatic Cystic and Alveolar Echinococcosis Management in Kazakhstan: A Nationwide Administrative Data Analysis (2023–2025) - Jamilya Saparbay; Zhanat Spatayev; Abylaikhan Sharmenov; Assylmurat Zhumukov; Chokhan Aytbayev; Adina Kulanbayeva; Gulnara Kulkayeva; Yuliya Semenova; Zhandos Burkitbayev; Assan Zhexembayev (International Journal of Environmental Research and Public Health, 2026)
Background: Kazakhstan is among the most highly endemic countries for hepatic echinococcosis worldwide, yet no study systematically characterised the national hepatobiliary surgical burden of cystic (CE) and alveolar (AE) echinococcosis using administrative health data. Methods: National operative data from the Guaranteed Volume of Free Medical Care (GOBMP) and Compulsory Social Health Insurance (OSHI) Systems (1 January 2023–31 December 2025) were combined with institutional case series from the National Research Oncology Center (NROC), Astana (2021–2025). Cases were identified using ICD-10 diagnosis codes and ICD-9-CM procedure codes. Regional and species-specific differences in surgical approach were assessed using Pearson’s chi-square test; continuous variables were compared using the Mann–Whitney U test. Results: A total of 143 hepatic echinococcosis surgeries were performed nationally over the three-year period, with a 12.8% increase in annual volume (47 in 2023, 43 in 2024, 53 in 2025), though this year-to-year variation was not statistically significant (χ2 = 1.06, df = 2, p = 0.59). CE accounted for 74.8% of cases (n = 107), AE for 18.9% (n = 27), and unspecified hepatic echinococcosis for 6.3% (n = 9); the proportion of AE rose from 17.0% in 2023 to 26.4% in 2025. Astana performed 46.2% of all operations nationally, with its share increasing from 34.0% to 58.5% over the study period; together with Almaty, it accounted for 92.6% of all AE cases. Partial hepatic resection was the predominant procedure overall (81.1%), while AE was managed exclusively by resectional or lobar procedures (χ2 = 15.37, p = 0.004), with no percutaneous approaches used. In the NROC case series (n = 63), AE patients were older (median 43.5 vs. 33 years, p = 0.036) and had longer postoperative hospital stays (median 12 vs. 10 days, p = 0.015) than CE patients. Conclusions: Surgical management of hepatic echinococcosis in Kazakhstan is increasingly centralised in Astana and Almaty, with AE consistently requiring more extensive resectional surgery and greater healthcare resource use than CE. These findings support the development of a national echinococcosis registry and formal referral pathways to guide resource allocation and surgical planning.